Experience in using injectable valproic acid (convulex) in patients with serial epileptic seizures and status epilepticus at the prehospital stage - A. V. Lebedeva; V. A. Karlov; A. M. Sidorov; V. L. Baratashvili; V. E. Khomutov (Неврология, нейропсихиатрия, психосоматика, 2014)
Objective: to evaluate the efficacy of injectable valproate (convulex) in patients with serial epileptic seizures and status epilepticus (SE) at the prehospital stage.Patients and methods. Thirty-two adult patients, including 17 (53%) men and 15 (47%) women, were examined. Most patients were aged over 40 years (mean age 54.7±9.4 years). To define the required dose of the drug, the authors estimated the patient's weight that averaged 76.8±1.9 kg, i.e. there was a preponderance of patients who needed convulex, more than 500 mg, to achieve a therapeutic effect.Results. It was impossible to reliably and validly evaluate the type of a seizure as the medical emergency team (MET) generally observed the patient with a just evolving seizure and the medical history data were not always valid therefore the type of convulsions and the type of a seizure were evaluated. In most cases, solitary convulsive attacks (tonic and/or clonic convulsions) and/or serial seizures were observed in 12 (37.5%) and 14 (43.7%) patients, respectively; SE was recorded in 6 (8.8%) patients. Generalized seizures (without a clear focal onset) were prevalent in 24 (75%) patients while 8 (25%) patients were found to have partial seizures (seizure onset lateralization, a focal onset). According to the pattern of convulsions, seizures may be classified into three types: tonic-clonic, clonic, and tonic in 22 (68.8%), 7 (21.9%), and 3 (9.3%) patients, respectively. Analysis of the efficacy of intravenously injectable valproate (convulex) in the group of patients with SE and epileptic seizures indicated that complete cessation of seizures could be achieved in 68.8%, their rate decreased in other 9.4% of the patients. Seizures were preserved in 7 (21.8%) cases, which required additional administration of drugs. Conclusion. Injectable valproic acid (convulex) has a high efficacy and may be preclinically used as the drug of choice to arrest SE and serial seizures caused by both epilepsy and other diseases of the brain. Convulex is easy-to-use (a ready-to-use solution), particularly in the work of MET. The ready-to-use formulation allows for its bolus administration within minutes, the drug does not affect hemodynamic parameters, which is particularly important for elderly patients and children. The administration of convulex makes it possible to prevent respiratory depression and fails to affect the level of patient consciousness.